Rola małej retencji w ochronie przeciwpowodziowej lubuskiego odcinka Odry = Meaning of small retention in assessing of flood hazards along the lubuski section of the Oder - Kołodziejczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Flood ramparts are basic way of flood protection. Theirs effective utili-zation can be yet reached only under condition of coherent water economy in whole drainage-basin. To limit possible economic losses, resulting from shortages of water and to improve structure of water balance simultaneously, one should to enlarge ruthlessly and to rebuild of retention ability of river purchase centre of dairy produce as well as to regain lost values of natural environment. Example of led workings in direction of enlargement retention of valleys are planned works on Lubuski section of Oder, described in this article.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007)